If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + y = 24 Solving -6x + y = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. -6x + y + -1y = 24 + -1y Combine like terms: y + -1y = 0 -6x + 0 = 24 + -1y -6x = 24 + -1y Divide each side by '-6'. x = -4 + 0.1666666667y Simplifying x = -4 + 0.1666666667y
| -2x^2+5=3x-3 | | 51=x+4x+(x+3) | | -4(4)+4y=16 | | 6+z*10=-2 | | 2x/7x=3 | | x(15x+4)=32 | | 6x-6=4x+10 | | 2x/8x=3 | | f(x)=x^3+6x^2+3x-10 | | -6(4)+y=24 | | -12(2n+11)=3(5n-5) | | 6x-1=27-x | | 5+log^4(-4x)=7 | | 3x+2(x-7)=(9x-1)-(x-8) | | -6x+(-6x+24)=24 | | 10x+8=158 | | 300=x+(x+20) | | n+3*8=-4 | | .5(4x-10)=15 | | (h-6)=2(5-2h) | | 2/7(x)= | | x+7=x-31 | | 29x-17y=-7 | | 7.3=y-6 | | 29x-17y=-7forx | | 2=(1+0.01)12n | | -1*2x-7=-11 | | 7x=5t+3 | | n/48=6 | | 2+{-5}= | | -4(-6v-1)=-40+2v | | -7/9w=35 |